(untitled) (Journal of Global Arts Studies, 2024)
Background: The integration of culture and tourism can effectively promote the transformation and upgrading of the agricultural and forestry product supply chain, thereby achieving efficient coordination and optimization of rural industrial resources. Objective: This study aims to build a robust and sustainable digital supply chain system, cultivate rural industries, optimize industrial structures, enrich rural economies, and ultimately promote comprehensive rural revitalization. Methods: Through field investigations and on-site research, the study identifies the current conditions and existing problems in the development and construction of rural industrial chains. Based on these findings, a digital supply chain model and corresponding elements for rural agricultural and forestry products are constructed, forming a hierarchical and clearly structured digital supply chain network. Results: The research proposes the establishment of a digital supply chain network suitable for the practical development of the rural economy through multi-party collaborative participation. This includes digital supply chain design, demand visualization, modernization of specialized cooperative operations, and the digitalization of risk management systems. Conclusion: The application of digital technology demonstrates significant value in promoting rural revitalization. It effectively facilitates the transformation and upgrading of rural industries, improves villagers’ living standards, and contributes to the construction of beautiful rural communities, thereby realizing the comprehensive revitalization of industries, organizations, talents, culture, and ecology.